Manifestations of Agricultural Activities & their Disputes in the Rural Territiry of the Islamic West in Light of the Book "Questions & Answers" by Daouidi (d. 402 AH / 1011 AD) -Reading on Issues of Crops, Gardens & Animals- - زياني , الصادق (Milev Journal of Research and Studies, 2023)
This study seeks to enumerate the various issues and disputes related to agricultural activities in the countries of the Islamic West during the 4th century AH/10th century through the book “el aseila & el adjwiba” by Abu Jaafar Ahmed ibn Nasr Daouidi M'sili, who died in 402 AH, by focusing on three topics: issues of crops, fruits, and animals. 28 issues were collected, and after classifying and analyzing them, we reached at the end of the study the type of jurisprudential discourse based on the Maliki doctrine through the nature and content of the answers that the jurist gave, aiming to establish justice between the disputing parties without any injustice or injustice by resorting to the opinions of many jurists Malikis, such as Imam Malik, Ibn al-Musayyab, Ibn al-Qasim, and others, for organizing rural life and agricultural activities in it according to the dictates of Sharia.